Analisis Determinan Kemiskinan di Provinsi Papua Tahun 2011-2020 - Arisanti Dewi Prasetyaningsih; Firsty Ramadhona Amalia Lubis; Nurul Azizah Az Zakiyyah (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2023)
Poverty is a complex issue in Indonesia, especially in remote areas far from the capital, such as Papua Province. Despite being known for its abundant natural resources, Papua is still the poorest province in Indonesia. There are many factors that contribute to poverty in Papua being the highest in Indonesia. Therefore, this study aims to analyze the factors that influence poverty in Papua Province, where the independent variables used consist of the Human Development Index, Regional Expenditure, Inflation, and Gross Regional Domestic Product. This study uses the EVIEWS-9 analysis tool using the random effects model approach. The data in this study comes from official sources such as the Central Statistics Agency, Ministry of Finance reports, and journals. The results of this study indicate that the Human Development Index variable has a negative and significant effect, inflation has a negative and insignificant effect, regional expenditure has a negative and insignificant effect, and Gross Regional Domestic Product has a negative and significant effect on poverty in Papua Province in 2011-2020.